Changes in Rat Brain MicroRNA Expression Profiles Following Sevoflurane and Propofol Anesthesia - Lu, Yu (Chin Med J (Engl), 2015)
BACKGROUND: Sevoflurane and propofol are widely used anesthetics for surgery. Studies on the mechanisms of general anesthesia have focused on changes in protein expression properties and membrane lipid. MicroRNAs (miRNAs) regulate neural function by altering protein expression. We hypothesize that sevoflurane and propofol affect miRNA expression profiles in the brain, expect to understand the mechanism of anesthetic agents. METHODS: Rats were randomly assigned to a 2% sevoflurane group, 600 μg·kg(−1)·min(−1) propofol group, and a control group without anesthesia (n = 4, respectively). Treatment group was under anesthesia for 6 h, and all rats breathed spontaneously with continuous monitoring of respiration and blood gases. Changes in rat cortex miRNA expression profiles were analyzed by miRNA microarrays and validated by quantitative real-time polymerase chain reaction (qRT-PCR). Differential expression of miRNA using qRT-PCR among the control, sevoflurane, and propofol groups were compared using one-way analysis of variance (ANOVA). RESULTS: Of 677 preloaded rat miRNAs, the microarray detected the expression of 277 miRNAs in rat cortex (40.9%), of which 9 were regulated by propofol and (or) sevoflurane. Expression levels of three miRNAs (rno-miR-339-3p, rno-miR-448, rno-miR-466b-1*) were significantly increased following sevoflurane and six (rno-miR-339-3p, rno-miR-347, rno-miR-378*, rno-miR-412*, rno-miR-702-3p, and rno-miR-7a-2*) following propofol. Three miRNAs (rno-miR-466b-1*, rno-miR-3584-5p and rno-miR-702-3p) were differentially expressed by the two anesthetic treatment groups. CONCLUSIONS: Sevoflurane and propofol anesthesia induced distinct changes in brain miRNA expression patterns, suggesting differential regulation of protein expression. Determining the targets of these differentially expressed miRNAs may help reveal both the common and agent-specific actions of anesthetics on neurological and physiological function.